2005
DOI: 10.1007/s10697-005-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Dynamics of a Centrifuged Fluid Layer

Abstract: The dynamics of a low-viscosity fluid layer inside a rotating cylinder under transverse translational vibration relative to the rotation axis is investigated experimentally. A novel vibrational effect, the generation of intense azimuthal fluid flows with velocities comparable with the cavity rotation velocity, is revealed. The structure and intensity of the vibrational flows and the flow transformation with variation of the determining dimensionless parameters (frequency and vibrational acceleration) are studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The retrograde motion excitation occurs similarly at n< 1 (solid triangles in Fig. 2) (Ivanova et al 2005).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…The retrograde motion excitation occurs similarly at n< 1 (solid triangles in Fig. 2) (Ivanova et al 2005).…”
Section: Introductionmentioning
confidence: 73%
“…So, the prograde motion in the cylinder frame is excited. On the contrary at n < 1 the retrograde one appears (Ivanova et al 2005). The considerable intensification of the mean flow takes place at some resonant frequencies when azimuth wave amplitude amplifies, so cylinder vibration produces 2D wave with azimuth wave number l = 1.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A systematic experimental research and analysis from the position of vibrational mechanics have shown that the centrifugal waves lead to the generation of a steady streaming in the Stokes boundary layers [ 17]. If a centrifuged liquid layer is subjected to the perpendicular vibrations, the resonant excitation of a two-dimensional azimuthal wave at the free surface is found [18] at the vibration frequencies, predicted by the theory [16]. The above-mentioned two-dimensional azimuthal wave is characteristic of various rotating two-phase systems.…”
Section: Introductionmentioning
confidence: 99%
“…The density inhomogeneity of such systems ensures the nontrivial inertial properties and, therefore, possibility of controlling them using the vibrations [1]. For instance the action of transverse vibrations on the free boundary of the centrifuged liquid [2] leads to the excitation of an azimuthal wave and excitation of intensive averaged liquid flow. Similar resonance effects occur when the free flowing medium [3] or a light cylindrical body [4] are in rotating system instead of a gas phase.…”
Section: Introductionmentioning
confidence: 99%